Improving Charge Injection at Gold/Conjugated Polymer Contacts by Polymer Insulator‐Assisted Annealing for Transistors. Issue 9 (16th December 2021) - Wei, Peng; Shen, Zichao; Qin, Xinsu; Zhang, Peng; Bu, Laju; Chen, Qing; Roth, Stephan V.; Lu, Guanghao
Abstract: The poor chemical miscibility between metal and organic materials usually leads to both structural and energetic mismatches at gold/organic interfaces, and thereby, high contact resistance of organic electronic devices. This study shows that the contact resistance of organic field‐effect transistors is significantly reduced by one order of magnitude, by reforming the contact interface between gold electrodes and conjugated polymers upon a polymer insulator‐assisted thermal annealing. Upon an optimized solution process, the conjugated polymer is homogenously distributed within the amorphous polymer insulator matrix with relatively low glass transition temperature, and thus, even a moderate annealing temperature can induce sufficient motion of conjugated polymer chains to simultaneously adjust the polymer orientation and improve the packing of gold atoms. Consequently, gold/conjugated polymer contact is reorganized after annealing, which improves both charge transport from bulk gold to interface and charge injection from gold into conjugated polymers. This method, with appropriate insulator matrix, is effective for improving the injection of both holes and electrons, and widely applicable for many unipolar and ambipolar conjugated polymers to optimize the device performance and simultaneously increase the optical transparency (over 80%). A frequency doubler and a phase modulator are demonstrated, respectively, using the ambipolar transistors with optimized charge injection properties. Abstract : A polymer insulator assisted‐thermal annealing method is proposed to reform the metal/conjugated polymer contact for high‐efficiency charge injection. Consequently, the contact resistance of polymer field‐effect transistors is reduced by one order of magnitude. This method is effective for improving the injection of both holes and electrons, and widely applicable for various unipolar and ambipolar polymer semiconductors.